Coverage of Malaysian Scholarly publications in the Directory of Open Access Journals: An exploratory study - Jinjin Liu,; Shen, Cenyu; Abdullah, Noorhidawati; Yanti Idaya Aspura Mohd Khalid,; Jiayi Xu, (Malaysian Journal of Library and Information Science, 2024)
The aim of this study is to assess the current status of Open Access journals published in Malaysia by analysing the Malaysian journals listed in the Directory of Open Access Journals (DOAJ). This exploratory and descriptive study is guided by the following research questions: (a) What growth trends are evident in Malaysian journals covered in DOAJ? (b) Are these journals also indexed in Web of Science (WoS), Scopus, and MyCite? (c) What are distribution, and publishing dynamics of Malaysian journals covered in DOAJ? Data was collected from DOAJ, with information on indexed journals prior to 2024. The performance of Malaysian journals listed in DOAJ was further evaluated using data from WoS, Scopus, and MyCite. A total of 101 Malaysian journals were identified, of which 27 are indexed in WoS (ESCI), 36 in Scopus, and 69 in MyCite. The publishers of these journals can be categorised into four groups: university publishers, commercial publishers, publishers affiliated with societies or associations, and government-affiliated publishers. Notably, public university publishers are the major players in Malaysian Open Access journals. Approximately two-thirds of the journals are concentrated in four main subject categories, indicating an unbalanced development across different fields. There remains significant room for improvement in the openness of these journals. This study provides an overview of Malaysian journals included in DOAJ and highlights their key characteristics. The findings can serve as a valuable reference for journal publishers in Malaysia striving to meet global standards for Open Access.